Experimental Study on Triaxial Unloading Failure of Deep Composite Coal-Rock - Xin Li; Hao Li; Zhen Yang; Zhongxue Sun; Jiayu Zhuang; Chongxiao Song; Xue Wang (Advances in Civil Engineering)
With the deep mining of coal, the phenomenon of high ground stress is more likely to cause dynamic disaster. In view of the above problems, this paper takes the unloading process of coal mining as the background to study the effects of mining rates under different conditions on the mechanical properties and triaxial failure criterion of composite coal-rock, so as to provide a theoretical basis for the prevention and control of dynamic disasters in coal mines. The composite coal-rock models with a composite ratio of 1 : 1 : 1 were tested under different unloading rates or confining pressures. The results show that the triaxial unloading process of coal-rock can be divided into five stages: compaction, single elasticity, elastic-plastic unloading, partial fracture, and complete fracture. In this paper, the failure criterion of composite coal-rock triaxial unloading is derived. The unloading rate has an exponential relationship with the triaxial compressive strength, and the relationship between initial confining pressure and compressive strength is linear. The triaxial compressive strength is determined by both. The peak strains ε of all samples under different unloading conditions were around 0.01. And initial confining pressure had an influence on the strain variation trend during the unloading of composite coal-rock. The higher the initial confining pressure, the greater the elastic modulus. In addition, an increase of initial confining pressure led to the increase of the total energy converted into dissipated part in the process of fracture and caused the obvious increase of the rebound characteristics of the curve. However, the unloading rate had no influence on the strain trend.